2015
DOI: 10.1186/s41043-015-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

The opioid effects of gluten exorphins: asymptomatic celiac disease

Abstract: Gluten-containing cereals are a main food staple present in the daily human diet, including wheat, barley, and rye. Gluten intake is associated with the development of celiac disease (CD) and related disorders such as diabetes mellitus type I, depression, and schizophrenia. However, until now, there is no consent about the possible deleterious effects of gluten intake because of often failing symptoms even in persons with proven CD. Asymptomatic CD (ACD) is present in the majority of affected patients and is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 86 publications
0
21
1
Order By: Relevance
“…Solute barrier function remains largely unchanged in NCGS, which is consistent with fairly normal adaptive immune response, normal intestinal permeability and expression of tight junction proteins[ 14 , 21 ]. Gluten’s opioid like effect on the intestinal transit time and nocebo effect has also been studied and may have an important role on the overall pathology and clinical presentation of the disease[ 31 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Solute barrier function remains largely unchanged in NCGS, which is consistent with fairly normal adaptive immune response, normal intestinal permeability and expression of tight junction proteins[ 14 , 21 ]. Gluten’s opioid like effect on the intestinal transit time and nocebo effect has also been studied and may have an important role on the overall pathology and clinical presentation of the disease[ 31 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Second, we know that when eating wheat, the gluten exorphins stimulate insulin production and is considered an endogenous opioid activity. 30 In nonobese diabetic (NOD) mice, bred for diabetes, the incidence of T1DM is 61%. In NOD mice, bred for diabetes, never given gluten, the incidence of T1DM is 6%.…”
Section: Dr Rountree: and It Is Different For Everybody?mentioning
confidence: 99%
“…Studies have shown that gluteomorphins act as opioid agonists on δ-type opioid receptors and consist of gluteomorphin A4, A5, B4, B5, C, and 7. These are resistant to the intestinal and enterobacterial proteinases, cross the human intestinal epithelium, enter the bloodstream, and interfere with the central nervous system [9,[43][44][45][46][47]. Gluteomorphin A5 has been associated with antinociceptive effect and modulation of memory process and affects peripheral nervous system and central nervous system.…”
Section: Opioid Peptides Derived From Plant/cereal Proteinmentioning
confidence: 99%